Study on Effect of Number of Transparent Covers and Refractive Index on Performance of Solar Water Heater - Kalidasan, B.; Srinivas, T. (Journal of Renewable Energy, 2014)
Liquid flat plate collector (solar flat plate collector) is one of the important applications in solar thermal system. The development in solar photovoltaic is an emerging challenge for the solar thermal system. In the current work an attempt has been made to optimize the number of transparent covers and refractive index to improve the optical efficiency and thermal efficiency for the collector. Performance of the liquid flat plate collector at VIT University Vellore has been simulated numerically for January 21st at an interval of half an hour with different numbers of transparent covers (0–3) and different refractive index values ranging from 1.1 to 1.7. The formulation and solutions are developed with simple software Microsoft Office Excel to result the performance characteristics. The result shows that the efficiency of the flat plate collector increases with an increase in number of covers and decreases after an optimum number of covers. It also decreases with an increase in refractive index. The combination of optimum number (two) and lower refractive index (1.1) results improved useful heat.